Additive Type Affects Fermentation, Aerobic Stability and Mycotoxin Formation during Air Exposure of Early-Cut Rye (Secale cereale L.) Silage - Horst Auerbach; Peter Theobald (Agronomy, 2020)
Whole-crop rye harvested before maturity represents a valuable forage for silage production. Due to the scarcity of data on fermentation characteristics and aerobic stability (ASTA) and the lack of information on mycotoxin formation during aeration of early-cut rye (ECR) silage after silo opening, we evaluated the effects of different additive types and compositions. Wilted forage was treated with various biological and chemical additives, ensiled in 1.5-L glass jars and stored for 64 days. Fermentation pattern, yeast and mould counts and ASTA were determined at silo opening. In total 34 mycotoxins were analysed in wilted forage and in silage before and after 240 h of air exposure. Chemical additives caused the lowest dry matter (DM) losses during fermentation accompanied with the lowest ethanol production and the highest water-soluble carbohydrate concentration. Aerobic deterioration, which started within two days after silo opening in silage left untreated and inoculated with homofermentative lactic acid bacteria, was prevented by the combined use of hetero- and homofermentative lactic acid bacteria and the chemical additive containing sodium nitrite, hexamethylene tetramine and potassium sorbate. Moreover, these two additives largely restricted the formation of the mycotoxin roquefortine C to < 0.05 mg kg−1 DM after aeration, whereas untreated silage contained 85.2 mg kg−1 DM.